2019
DOI: 10.1177/0954411919880694
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of rigid, semi-rigid and flexible spinal stabilization devices: A finite element study

Abstract: Pedicle-screw-based spinal fixation system has shown its success for treating degenerative disc disease-related back pain and spinal instability. In the last few decades, several non-fusion implants ( ‘flexible’ or ‘dynamic’ fixation) are developed for treating slight degenerate disc disease. The aim of this study is to characterize and compare the biomechanical responses of pedicle-screw-based fusion with various rod materials and a flexible spinal stabilization device on the lumbar spine (L3L5). Computed tom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 28 publications
1
12
0
Order By: Relevance
“…This is consistent with our previous results from in vitro mechanics tests on fresh cadaver specimens 11 . It was suggested that fusion surgery would seriously affect the physiological motor function of the lumbar spine at the surgical site and increase the intervertebral disc ROM in the adjacent segments, which was consistent with the previous research results of Biswas, JK et al 21 . Although the ROMs of the adjacent discs to the surgical site were reduced in the nonfusion group compared with those in the intact group, the difference between the two groups was not obvious.…”
Section: Discussionsupporting
confidence: 90%
“…This is consistent with our previous results from in vitro mechanics tests on fresh cadaver specimens 11 . It was suggested that fusion surgery would seriously affect the physiological motor function of the lumbar spine at the surgical site and increase the intervertebral disc ROM in the adjacent segments, which was consistent with the previous research results of Biswas, JK et al 21 . Although the ROMs of the adjacent discs to the surgical site were reduced in the nonfusion group compared with those in the intact group, the difference between the two groups was not obvious.…”
Section: Discussionsupporting
confidence: 90%
“…Although both types of rods can significantly reduce the mobility of the fixed segment (> 70%), PEEK rods can provide greater all-directional mobility than can titanium rods [ 20 22 ]. The finite element analysis showed that compared with titanium rods, PEEK rods can increase the range of flexion and extension, lateral flexion and axial rotation by 1.8-2.1, 7-7.2 and 3.7-3.8 times, respectively [ 23 , 24 ]. Biswas et al [ 24 ] performed finite element analysis and reported that the mobility of the fixed segment of PEEK rods was 4.2°-6.2° in flexion and 4.2°-1.1° in extension.…”
Section: Discussionmentioning
confidence: 99%
“…To simulate physiological flexion, extension, lateral bending and axial rotational motions, 2, 4, 6, 8 and 10 Nm bending moment are applied on L1 vertebrae to implanted (FRD) and intact (natural) models. 20…”
Section: Methodsmentioning
confidence: 99%
“…To simulate physiological flexion, extension, lateral bending and axial rotational motions, 2, 4, 6, 8 and 10 Nm bending moment are applied on L1 vertebrae to implanted (FRD) and intact (natural) models. 20 Multilinear stress-strain curve Ligaments [16][17][18] Young's modulus (MPa) Poisson's ratio Anterior longitudinal ligament (ALL) 7.8 (ε < 12%) 20 (ε > 12%) 0.3 Posterior longitudinal ligament (PLL)…”
Section: Boundary Conditionmentioning
confidence: 99%